Respuesta :
hello :
16x² + 8x - 15 = 16(x²+(1/2)x)-15
= 16(x²+1/2x+1/16-1/16)-15
= 16((x+1/4)² - 1/16)-15
= 16(x+1/4)²-1-15
=16(x+1/4)²-16
=16((x+1/4)²-1²)
=16(x+1/4-1)(x+1/4+1)
=16(x-3/4)(x+5/4)
=16/16(4x-3)(4x+5)
Factor completely, is :
16x² + 8x - 15 = (4x-3)(4x+5)
16x² + 8x - 15 = 16(x²+(1/2)x)-15
= 16(x²+1/2x+1/16-1/16)-15
= 16((x+1/4)² - 1/16)-15
= 16(x+1/4)²-1-15
=16(x+1/4)²-16
=16((x+1/4)²-1²)
=16(x+1/4-1)(x+1/4+1)
=16(x-3/4)(x+5/4)
=16/16(4x-3)(4x+5)
Factor completely, is :
16x² + 8x - 15 = (4x-3)(4x+5)